Chromosomal causes of hypergonadotropic hypogonadism in women and men. Literature review - О. А. Бурка; Л. П. Кузьмук; Г.О. Ісламова; С. В. Овчаренко (Publishing House TRILIST, 2020)
Despite the relatively small portion in the structure of the infertility causes, hypergonadotropic hypogonadism (HH) is one of the greatest challenges in reproductive medicine. Diagnosis of HH chromosomal causes often occurs with a significant delay. This is due to the widespread stereotype of the necessary presence of typical phenotypic characters (eunuchoid habitus, pterygoid folds on the neck). This review deals with clinical recommendations for diagnosis of the most common chromosomal causes of HH in women (Turner syndrome (TS)) and in men (Klinefelter syndrome (KS)). TS is a chromosomal pathology associated with the complete or partial absence of one X chromosome accompanied by one or more specific phenotypic features and comorbidities. Persons with suspected TS need to have karyotyping of at least 20 cells (venous blood material). This allows determining the karyotype 45,X, structural anomalies of X chromosome and mosaicism if it is present in more than 10% of the cells. If the mosaic form of TS is suspected but not diagnosed with standard karyotyping, options for investigating more cells or fluorescence hybridization in situ (FISH) are possible. It is important to verify the mosaic forms, especially in cases of a clone with Y chromosome in TS, since such a karyotype carries an increased risk of gonadoblastoma. FISH increases the diagnostic rate of mosaic forms of aneuploidy. Primary hypogonadism in men is the insufficiency of testosterone synthesis and spermatogenesis failure due to the pathology of gonads. Chromosomal causes of primary hypogonadism and nonobstructive azoospermia account for about 15% and are included in the mandatory list of diagnostic examinations. The variants of karyotypes in KS and their clinical manifestations are considered. KS is much more often diagnosed with delay compared to TS. The main diagnostic method for KS is karyotyping and using FISH to detect mosaic forms. Thus, cytogenetic testing (karyotyping) is the first line of examination for women and men with primary (non-iatrogenic) HH; the use of FISH increases the diagnostics efficiency of mosaic forms of sex chromosome aneuploidy.